2018
DOI: 10.3390/app8020281
|View full text |Cite
|
Sign up to set email alerts
|

Bi-Functionalized Clay Nanotubes for Anti-Cancer Therapy

Abstract: Systemic toxicity is an undesired consequence of the majority of chemotherapeutic drugs. Multifunctional nanoparticles with combined diagnostic and therapeutic functions show great promise towards personalized nanomedicine. Halloysite clay nanotubes (HNTs) have shown potential as a drug delivery vehicle, and its surface can be modified and tailored as a targeted drug delivery system. In this short report, we modified the HNT surface by covalently bonding folic acid (FA) and fluorescein isothiocyanate (FITC). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In our previous study [ 16 ], we assessed bi-HNTs cytotoxicity and observed that cytotoxicity increased with bi-HNT concentration. In order to confirm the optimal dosage range for bi-HNTs, we used an MTS assay and XTT assay to assess cell proliferation and viability with cells co-cultured with pure HNTs and bi-HNTs at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study [ 16 ], we assessed bi-HNTs cytotoxicity and observed that cytotoxicity increased with bi-HNT concentration. In order to confirm the optimal dosage range for bi-HNTs, we used an MTS assay and XTT assay to assess cell proliferation and viability with cells co-cultured with pure HNTs and bi-HNTs at different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…bi-HNTs were synthesized using the same methods as described in a previous study ( Figure 2 ) [ 16 ]. Briefly, HNTs (Sigma Aldrich, St. Louis, MO, USA) were reacted at reflux with N -[3-(trimethoxysilyl) propyl] ethylenediamine (DAS) (Sigma Aldrich, St. Louis, MO., USA) in toluene for 24 h. Then, the HNT-DAS composite was reacted with FA (Sigma Aldrich, St. Louis, MO, USA) in the presence of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) (Sigma Aldrich, St. Louis, MO, USA) in DI water overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hollow tubular shape and peculiar surface properties make HNTs suitable as catalytic supports for several reactions [29][30][31][32][33][34] as well as adsorbent systems for wastewater decontamination [35][36][37][38]. Filling polymeric matrices with halloysite presents as a successful strategy to obtain functional nanocomposite materials with excellent characteristics in terms of mechanical performance [39,40], thermal stability [10,41,42], and vapor barrier properties [43].The unique behavior of HNTs allows for selective modification with functional molecules; promising for the preparation of organic/inorganic composites [44,45]. The opposite charges of the inside and outside surfaces allow for the selective adsorption of anionic or cationic surfactants presenting as an easy strategy to prepare new advanced hybrid materials [46,47].…”
mentioning
confidence: 99%
“…The unique behavior of HNTs allows for selective modification with functional molecules; promising for the preparation of organic/inorganic composites [44,45]. The opposite charges of the inside and outside surfaces allow for the selective adsorption of anionic or cationic surfactants presenting as an easy strategy to prepare new advanced hybrid materials [46,47].…”
mentioning
confidence: 99%